Changes in anterior chamber depth and intraocular pressure after phacoemulsification in eyes with occludable angles - Shin, H.C.; Subrayan, V.; Tajunisah, I. (Elsevier, 2010)
PURPOSE: To evaluate changes in anterior chamber depth (ACD) and intraocular pressure (IOP) after phacoemulsification in eyes with occludable angles and compare the results with those in eyes with normal open angles. SETTING: Eye Clinic, Ipoh General Hospital, Ipoh, Perak, Malaysia. METHODS: Patients with nonglaucomatous eyes with open angles or with occludable angles were recruited. Ocular biometric measurements (ACD, axial length [AL], lens thickness and position) and IOP (tonometry) were performed preoperatively and 1 day and 1, 4, 9, and 12 weeks postoperatively. RESULTS: The open-angle group and occludable-angle group each comprised 35 patients. The occludable-angle group had a shallower ACD, shorter AL, thicker and relatively anterior lens position, and higher IOP preoperatively; postoperatively, there was a significant increase in ACD and a significant reduction in IOP (P<.01). Anterior chamber deepening was inversely related to preoperative ACD in the occludable-angle group (P<.01). The mean preoperative IOP was higher in the occludable-angle group (15.77 mm Hg +/- 2.20 [SD]) than in the open-angle group (14.52 +/- 2.65 mm Hg) (P<.05). The IOP dropped progressively and significantly over 12 weeks postoperatively; the mean decrease was 2.31 +/- 0.99 mm Hg in the occludable-angle group and 0.77 +/- 1.17 mm Hg in the open-angle group. The IOP decrease in the occludable-angle group was inversely related to the preoperative IOP (P<.01). CONCLUSION: Phacoemulsification led to anterior chamber deepening and lower IOP in eyes with occludable angles, which suggests it is an option for preventing acute angle closure attacks in eyes with occludable angles and cataract.